2010
DOI: 10.1088/0004-637x/711/1/192
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Dependence of the Evolving S0 Fraction

Abstract: We re-investigate the dramatic rise in the S0 fraction, f S0 , within clusters since z ∼ 0.5. In particular, we focus on the role of the global galaxy environment on f S0 by compiling, either from our own observations or the literature, robust line-of-sight velocity dispersions, σ s, for a sample of galaxy groups and clusters at 0.1 < z < 0.8 that have uniformly determined, published morphological fractions. We find that the trend of f S0 with redshift is twice as strong for σ < 750 km s −1 groups/poor cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
70
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 50 publications
(86 reference statements)
8
70
0
Order By: Relevance
“…They find that the combined tidal interaction can have a significant impact on the morphology of galaxies, inducing series of bursts of star formation that increase the stellar mass in the central bulges. These results suggest that groups are suitable environments where S0 galaxies can be formed, in line with implications from observational evidence Just et al 2010). …”
Section: Introductionsupporting
confidence: 80%
“…They find that the combined tidal interaction can have a significant impact on the morphology of galaxies, inducing series of bursts of star formation that increase the stellar mass in the central bulges. These results suggest that groups are suitable environments where S0 galaxies can be formed, in line with implications from observational evidence Just et al 2010). …”
Section: Introductionsupporting
confidence: 80%
“…It has also been studied the properties of galaxies in the infalling region at intermediate/high redshifts. Just et al (2015) found evidences of preprocessing of galaxies in the infall region of clusters in the redshift range 0.4 < z < 0.8. These authors found that at z ∼ 0.6, the fraction of red galaxies in the infall region is larger than in the field (see also Moran et al 2007 andPatel et al 2011) In this paper, we study the population of galaxies in the infalling region of massive groups taken from Zandivarez & Martínez (2011).…”
Section: Introductionmentioning
confidence: 94%
“…Poggianti et al 2008;Fumagalli & Gavazzi 2008) or the emergence of lenticular galaxies (S0) and corresponding decline in spirals (e.g. Desai et al 2007;Just et al 2010). Although spiral disc fading is not a sufficient explanation for the rise of S0s (Christlein & Zabludoff 2004), spirals are strongly affected both in numbers and properties by dense environments.…”
Section: Introductionmentioning
confidence: 99%